Interaction between focal adhesion kinase and Crk-associated tyrosine kinase substrate p130Cas. - Polte, T R (1995)
The focal adhesion kinase (FAK) has been implicated in integrin-mediated signaling events and in the mechanism of cell transformation by the v-Src and v-Crk oncoproteins. To gain further insight into FAK signaling pathways, we used a two-hybrid screen to identify proteins that interact with mouse FAK. The screen identified two proteins that interact with FAK via their Src homology 3 (SH3) domains: a v-Crk-associated tyrosine kinase substrate (Cas), p130Cas, and a still uncharacterized protein, FIPSH3-2, which contains an SH3 domain closely related to that of p130Cas. These SH3 domains bind to the same proline-rich region of FAK (APPKPSR) encompassing residues 711-717. The mouse p130Cas amino acid sequence was deduced from cDNA clones, revealing an overall high degree of similarity to the recently reported rat sequence. Coimmunoprecipitation experiments confirmed that p130Cas and FAK are associated in mouse fibroblasts. The stable interaction between p130Cas and FAK emerges as a likely key element in integrin-mediated signal transduction and further represents a direct molecular link between the v-Src and v-Crk oncoproteins. The Src family kinase Fyn, whose Src homology 2 (SH2) domain binds to the major FAK autophosphorylation site (tyrosine 397), was also identified in the two-hybrid screen.